Challenges In Implementing Integrated Electronic Health Records (EHRS) in Namibia’s Public Health Sector - Shonghela, Victoria Mwetunyenena; Kamati, Etuna (Journal of Information Systems and Informatics, 2025)
The study was aimed at investigating the challenges of implementing integrated Electronic Health Records (EHR) in the Namibian Public Health Care Sector. The study employed qualitative research approach. An exploratory design was used in this study to engage IT Personnel. The study used the purposive sampling technique to select twenty respondents, particularly focusing on the IT department. The study discovered that the Ministry of Health and Social Services (MoHSS) have isolated Electronic Health Record Systems (EHRS) such as the DHIS2 and Ptracker. The MoHSS had attempted to implement integrated EHRS, however it experienced various challenges. This study discovered challenges such as lack of network infrastructure, computer literate personnel, inadequate IT personnel, lack of policies and project documentation to implement the health records. Another challenge that hindered the addressing of issues such as supply of all up-to-date computer devices and software; having proper filing system and improving the slow connection due to poor network infrastructures is budget constraints. The study further discovered a lack of interoperability and standardization, the absence of unique identifiers for patients and the lack of data warehousing to be the main barriers for the full implementation of the integrated electronic health records system. Some of the recommendations of the study are that the MoHSS develops national policies and implementation frameworks to guide the implementation of EHRS, secure adequate funds specifically for the implementation of EHRS, develops and implements training framework for IT staff, administrative and health professional, implements unique patient identifier system and utilize open standards to enable system interoperability for implementation of the e-Health Record System. The study also recommends that MoHSS consider partnering with private service providers to enter into network infrastructure sharing agreements.